2020
DOI: 10.3390/w12113072
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Evaluation of the Latest High-Resolution Precipitation Products over the Upper Blue Nile River Basin, Ethiopia

Abstract: Quality and representative precipitation data play an essential role in hydro-meteorological analyses. However, the required reliability and coverage is often unavailable from conventional gauge observations. As a result, globally available precipitation datasets are being used as an alternative or supplementary to gauge observations. In this study, the accuracy of three recently released, high-resolution precipitation datasets with a spatial resolution of 0.1° and a daily temporal resolution is evaluated over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 38 publications
3
6
0
Order By: Relevance
“…However, all other products were inappropriate with respect to spatial and temporal variation of precipitation over the study area, with similar outcomes found in the previous findings of certain studies [37][38][39]. The temporal estimations of SM2Rain were in better agreement with gauge estimation, which is consistent with the findings of a particular study [10,24]. On a monthly scale, All SPPs estimations were in better agreement with gauge estimations as compared to the daily scale, which is comparable with previously documented studies [22,40,41].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, all other products were inappropriate with respect to spatial and temporal variation of precipitation over the study area, with similar outcomes found in the previous findings of certain studies [37][38][39]. The temporal estimations of SM2Rain were in better agreement with gauge estimation, which is consistent with the findings of a particular study [10,24]. On a monthly scale, All SPPs estimations were in better agreement with gauge estimations as compared to the daily scale, which is comparable with previously documented studies [22,40,41].…”
Section: Discussionsupporting
confidence: 90%
“…The uncertainty analysis of selected SPPs showed that their accuracy completely depends upon the in-situ topographical and environmental conditions. Previously, numerous researchers assessed the accuracies of many SPPs (SM2Rain, GPM-SM2Rain, CCI, ASCAT, and IMERG) over different parts of the earth [10,17,18]. The results of previous studies also indicated that the performance of SPPs was strongly influenced by the topography and climatic conditions of the study area [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The average annual precipitation increases from the eastern to southern direction. This pattern of increasing precipitation from eastern and northeastern portions of the basin to southern and southwestern portions is reported in Abtew et al (2009), Abebe et al (2020) and Abera et al (2017).…”
Section: Precipitation Distributionsupporting
confidence: 58%